Nitric Oxide and von Willebrand Factor Levels as Markers of Endothelial Dysfunction in Liver Cirrhosis - Juwita Sembiring; Suara Ginting; Abiran Nababan; Lukman Hakim Zain; Pengarapen Tarigan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
Introduction: A number of investigators have shown that endothelial dysfunction in liver cirrhosis can be indicated by increased levels of nitric oxide (NO) and von Willebrand factor (vWF). The cause of this increase is still unclear. It is believe to be correlated with hyperdinamic circulation and endotoxemia, which are common in liver cirrhosis. The Aim of This Study: To compare the levels of NO and vWF in liver cirrhosis patients with those in healthy control subjects, and to investigate whether there is a correlation between levels of NO and vWF with the severity of the disease according to the Child Pugh Criteria Material and Method: This study was conducted from February until June 2001 in 35 liver cirrhosis patients at Dr. Pirngadi and H. Adam Malik Hospital and some private hospitals in Medan. The mean age of patients with liver cirrhosis was 54  + 12.26 years, the youngest being 31 years and the oldest 75 years, and 20 healthy controls while the mean age of the control subject was 55.20 + 13.04 years, the youngest being 31 years and the oldest 76 years. Based on Child Pugh criteria, 9 were classified as Child Pugh class A, 13 in class B, 13 in class C. The criteria for liver cirrhosis were based on clinical examination, laboratory findings and liver ultrasound examination. Cirrhotic patients with hypercolestrolemia, hypertension, heart failure, myocardial infraction, renal failure diabetes, COPD were those on drugs, such as antibiotics and branchodilators were excluded from the study. Result: The mean level of NO in patients with liver cirrhosis was 6.2600  + 4.4456 mM, while the mean NO level in control subjects was 3.2325  + 3.2355 mM, p0.05. The mean level of NO in Child Pugh class A patients was 6.6889  + 3.9757mM, compared to control p0.05; in Child Pugh class B the mean level was 4.8308  + 2.4642 mM compared to control p0.05. There was a significant increase in the level of NO associated with the severity of liver cirrhosis. The mean level of vWF in patients with liver cirrhosis was 399.514  + 175.313% while the mean vWF level in control subjects was 139.100 + 51.144%, p0.05. The mean level of vWF in Child Pugh class A patients was 231.778 ± 43.8576%, compared to control p0.05; in Child Pugh class B was 365.846 + 110.034%, compared to control p0.05, in Child Pugh class C was 549.308 + 164.483%, compared to control p0.05. There was significant increase in the level of vWF correlated with severity of liver cirrhosis. Conclusion: The level of NO was significant higher in liver cirrhosis patients compared to control subjects, but there was no correlation between the increase in the level of NO with the severity of the disease. The levels of vWF was significantly higher in liver cirrhosis patients compared to control, and there was a correlation between increased levels of vWF and the severity of the disease.  Key Words: Liver cirrhosis, Child Pugh criteria, nitric oxide (NO), von Willebrand Factor (vWF)